System and method for preparing polymer-carbon nanomaterial blends from carbon dioxide and products thereof

By using the molten electrolysis process in polymers, the problems of high cost and high carbon footprint in polymer-CNM blend production are solved, achieving uniform dispersion and performance improvement of CNM.

CN117500957BActive Publication Date: 2025-03-14DIRECT AIR CAPTURE LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280037612.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-24
Filing Date
2022-05-24
Publication Date
2025-03-14
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

In the prior art, the commercial production of polymer-carbon nanomaterial (CNM) blends is limited by high cost and high carbon footprint, and there are technical challenges in uniform dispersing CNMs in the blend.

Method used

Carbon-alkane gels are produced from carbon dioxide (CO2) through a melt electrolysis process, which reduces the production cost of CNM and helps achieve uniform dispersion of CNM in the blend by providing a lattice-like structure.

Benefits of technology

Low-cost production of polymer-CNM blends is achieved, and the performance of the material is improved, including strength, electrical conductivity and thermal conductivity, etc. by uniformly dispersing CNM.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117500957B_ABST
    Figure CN117500957B_ABST
Patent Text Reader

Abstract

Embodiments of the present disclosure relate to apparatus, systems, and methods for preparing blends of polymers and carbon nanomaterials (CNMs). The blends of the embodiments contain about 10% or less CNM by weight (wt%). The CNM content of the blend can impart new or enhanced properties to the blend and materials and products made therefrom. The new or enhanced products can include enhanced tensile strength, new or enhanced electronic medical, structural thermal, catalytic properties, or any combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application Serial No. 63 / 192,304, filed on May 24, 2021, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to making products using an electrolytic process. Specifically, the present disclosure relates to a method of making a carbanogel blend product from carbon dioxide that is dissociated using an electrolytic process. Background Art

[0004] As of 2015, the annual production of plastics can be summarized as follows: polypropylene (PP), with 68 megatons (MT) of non-fibrous PP and 52 MT of fibrous PP produced; polyethylene (PE), with 64 MT of low-density PE and 52 MT of high-density PE produced; polyester, also known as polyethylene terephthalate (PET), with an annual production of 33 MT; polyvinyl chloride (PVC), with an annual production of 38 MT. Compared with PVC, the production of other plastics has dropped significantly.

[0005] During the production of plastics, the polymerization of monomers to form polymers occurs by reactions such as condensation reactions, ring opening reactions, ionic reactions, chain transfer reactions or plasma polymerization. Polymers are usually distinguished as natural polymers, synthetic polymers, semisynthetic polymers, recycled polymers, amorphous polymers, semicrystalline polymers, thermoplastics or thermosets.

[0006] The main advantages of PP and PE production are low cost and providing plastics with desirable mechanical flexibility. PP and PE are made by high temperature and high pressure gas with special catalysts. PP and PE face recycling challenges, they are chemically resistant plastics, which can cause PP and PE to stay in the environment and increase plastic pollution.

[0007] PVC is usually made by cooling, initiators, and one or more additives that help suspend small PVC particles in water. The aqueous suspension is then dried and melted together. Sometimes, PVC particles are produced first and then mixed with plasticizers or other additives in a slurry. This polymerization reaction does not produce anything beyond PVC. Typically, plasticizers and carbonates are added to increase PVC strength, flexibility, and the rate and ease of PVC production.

[0008] Thermoplastics are generally associated with materials that require rigidity. Thermoplastic materials can be melted by heating and cooled to resolidify, and formed into various forms by molding, compression molding, machining or by 3D printer application. Polylactic acid (PLA) is an example of a recyclable thermoplastic that can be bio-derived and sometimes biodegradable. PLA is relatively easy to manufacture by simple heating and produces water as a byproduct. The main limitation of PLA is its lower strength properties. Plasticizers are often used as additives to increase the desired properties in PLA, including polycarboxylates (or polycarboxylates) or citric acid with many carboxylate groups.

[0009] PLA (2019) has an annual production of only 0.2MT, but has the highest annual production growth rate (26%), demand exceeds supply, and prices rise. As a thermoplastic, PLA is a polymer that can be melted by heat and cooled and formed, a property shared by all thermoplastics including but not limited to the following: PE, PP, PVC, acrylic, acrylonitrile-butadiene-styrene or ABS, nylon, Teflon, and polycarbonate or PC. ABS is a commonly used plastic in 3D printing applications and is also used in car bodies, electrical appliances, and phone housings.

[0010] In contrast, thermosetting plastics are irreversibly cured into a permanent solid state by cross-linking, and are formed by chemical reactions. For example, thermosetting plastics can also be printed in 3D printing applications, but only by chemical reactions, such as but not limited to photopolymerization or thermochemical reactions. Before curing, one or more thermosetting plastic pre-curing components are obtained as liquids, which are generally viscous or dense. Thermosetting plastics are generally tolerant to higher temperatures and tend to decompose at high temperatures rather than melt. Common examples of thermosetting plastics include epoxy compounds (and epoxy resins), acrylic resins, phenolic resins, silicones (polysiloxanes), polyurethanes (PU), polyimides, vulcanized rubbers, Bakelite (polyoxybenzyl methylene ethanol anhydride), polydicyclopentadiene (pDCPD), polyisocyanurates, polyesters, polyureas, urea-formaldehyde and vinyl esters, cyanates, melamine or polyester resins.

[0011] Carbon nanomaterials (CNMs) including carbon nanotubes (CNTs) have been added to plastics to form admixtures, also referred to herein as admixtures, and composite materials and products can be made from such admixtures. Historically, PVC-CNT and PLA-CNT blends have been made by dissolving the plastic in a solvent and dispersing the CNTs therein by ultrasonication, then drying the blend, or melting the plastic beads mixed with the CNTs.

[0012] Polymer-CNT blends have been studied using PLA (including printed PLA / CNT compositions), PVC, and other polymers including polyurethanes, polystyrene, polyaniline, polyvinylidene fluoride, and a wide range of epoxides. Graphene and graphene oxide polymer blends are also known.

[0013] Kevlar is neither a thermoset nor a thermoplastic because it is formed by spinning a solution of a polymer into fibers. Kevlar-CNT composites are formed by coating Kevlar on CNTs and combining the CNTs with repeating units of the polymers p-phenylene terephthalamide (PPPA) and terephthaloyl chloride (TPC) covalently bound to the surface of the CNTs. Kevlar-CNT blends can significantly increase their impact resistance. Adding 0.1 weight percent (wt%) CNTs causes a 6.5-fold increase in normalized absorbed energy compared to no CNTs added.

[0014] Although it is known to combine CNMs and polymers to impart many new and enhanced properties to the resulting materials or products, the use and deployment of such resulting materials and products have not been extensive. Without being bound by any particular theory, this hindered use and deployment may be due to the common way of manufacturing CNM components, which has associated high costs and associated high carbon footprints. For example, chemical vapor deposition (CVD) is a process routinely used in the commercial production of CNMs. CVD is expensive, and currently, the price of CNMs such as CNTs, graphene, and carbon nano-onions ranges from $100,000 to $10 million per ton. In contrast, the price of steel is $400 to $700 per ton.

[0015] Therefore, new methods for the commercial production of polymer-CNM blends and materials and products made therefrom that address the high cost and associated high carbon footprint are desired. Summary of the invention

[0016] Embodiments of the present disclosure are directed to polymer-carbon nanomaterial (CNM) blends that can be used to prepare materials or products having new or enhanced properties compared to materials or products made from the polymer alone.

[0017] Some embodiments of the present disclosure relate to a method for preparing a polymer-CNM blend. The method includes the following steps: receiving a carboalkane gel; combining the carboalkane gel with a polymer mixture; and collecting (also referred to as recovering) the polymer-CNM blend.

[0018] Some embodiments of the present disclosure relate to polymer-CNM blends comprising carbene gel; and a polymer mixture.

[0019] Some embodiments of the present disclosure relate to a system for preparing a polymer-CNM blend. The system includes an apparatus for performing an electrolysis process that dissociates carbon dioxide (CO2) in a molten electrolyte to produce a carbamate gel, wherein the carbamate gel includes a carbon nanomaterial (CNM) and an electrolyte; a container for receiving the carbamate gel; and a polymer mixture source.

[0020] The deployment of polymer-CNM blends and resulting composites is hampered by the high cost of preparing the CNM component with an associated high carbon footprint. In addition, there are technical challenges in establishing a uniform dispersion of the CNM throughout the blend, especially when smaller amounts of CNM are present.

[0021] The high production costs of CNMs are known to be primarily due to high reactant and energy costs. Without being bound by any particular theory, according to embodiments of the present disclosure, when produced from CO2 by a molten electrolysis process, these production costs can be reduced by two orders of magnitude, and the CNMs produced can be used as a component in polymer-CNM blends. In addition, and without being bound by any particular theory, carbene gels produced by an electrolysis process can also help overcome the challenge of establishing a uniform dispersion of CNMs throughout a blend by providing a lattice-like structure of the carbene gel that can provide fixed and dispersed locations for the CNMs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] These and other features of the present disclosure will become more apparent in the following detailed description taken in conjunction with the accompanying drawings.

[0023] Figure 1 is a schematic diagram of an apparatus for preparing a carbamate gel product according to an embodiment of the present disclosure.

[0024] Figure 2 is a schematic diagram of a system for preparing polymer-CNM blends according to an embodiment of the present disclosure.

[0025] Figure 3 is a schematic diagram showing steps of a method according to an embodiment of the present disclosure.

[0026] Figure 4 There are two panels showing properties of embodiments of the present disclosure, wherein the upper panel shows photographs of epoxy articles prepared with and without carboalkane gel, and the lower panel shows the increased tensile strength relative to the weight percent addition of carboalkane gel.

[0027] Figure 5 A photograph showing a scanning electron microscope image of a carbene gel prepared according to an embodiment of the present disclosure is shown, wherein: Figure 5 A shows an image magnified by x730; and Figure 5 B shows the image magnified by x8600.

[0028] Figure 6 There are two insets showing schematic diagrams of other schemes for preparing polymer-CNM blends according to embodiments of the present disclosure, wherein the upper inset shows a scheme in which the combining step occurs before preparing the polymer, and the lower inset shows a scheme in which the combining step occurs after preparing the polymer. DETAILED DESCRIPTION

[0029] Embodiments of the present disclosure relate to devices, systems and methods for preparing blends of polymers and carbon nanomaterials (CNMs). The blends of the embodiments contain about 10% or less CNM by weight (wt%). The CNM content of the blend can impart new or enhanced properties to the blend and materials and products made therefrom. Such new or enhanced properties include, but are not limited to, strength properties, electronic application properties, medical application properties, thermal conductivity properties, thermal insulation properties, catalytic properties, or any combination thereof.

[0030] Energy efficient conversion of CO2 to carbon and oxidation by molten carbonate electrolysis has been known since 2009. Subsequently, chemical conversion of CO2 to various graphitic carbon nanomaterials (CNMs) was demonstrated. These graphitic CNMs are valuable due to long term stability, and these materials have useful properties such as ultra-high strength, high electrical conductivity, high thermal conductivity, new electronic devices, high battery, fuel cell and capacitor storage capacity, electromagnetic radiation shielding, effective drug delivery and various medical properties, and useful catalytic properties.

[0031] CO2→C 纳米材料 +O2 (Equation 1)

[0032] Equation 1 shows the melt electrolysis process, whereby carbon nanomaterials grow and remain on the cathode as a mixture of entangled CNMs mixed with electrolyte. This mixture is called carbene gel, from which at least 95% of the electrolyte can be pressed out by high temperature filter pressing.

[0033] Including graphene and single or multi-layer graphene sp 2The bonded carbon component (which may be present in the CNM component) can provide CNM enhanced properties in the carboalkane gel, such as, but not limited to, increased strength and conductivity of these CNMs. In addition, the relative amount of a specific morphology of the CNM can impart additional properties to the carboalkane gel and the products prepared therefrom. Examples of such morphologies include, but are not limited to, nanocarbons such as spherical nanocarbons, solid and hollow nano-onions, cylindrical allotropes, planar allotropes, spiral allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanosheets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface-modified or metal-coated CNMs, amorphous nanocarbons without graphitic features or properties, or any combination thereof. Examples of such additional properties include, but are not limited to, reduced friction, resilience, thermal conductivity, flame retardancy, chirality, enhanced surface area of ​​the CNMs in the carboalkane gel, or any combination thereof. These properties are useful for specific applications, including but not limited to: lubrication, flexible materials, chiral light absorption, chiral light emission, chiral catalysis, improved electrochemical charge storage, enhanced catalytic activity, fire resistance, or enhanced EMF shielding capabilities. The CNMs within the carbene gel may also include additional features, including doping, magnetism, unusual shapes, and reduced or enlarged sizes. Without being limited by any theory, the CNTs may include single-walled CNTs; multi-walled CNTs; doped CNTs, such as boron, sulfur, phosphorus, or nitrogen doped CNTs; magnetic CNTs; bamboo-shaped CNTs; pearl-shaped CNTs; isotope-specific CNTs, such as 12 C and 13 C CNTs; surface modified or metal coated CNTs; helical CNTs, including single or double braided CNTs; helical CNTs; thin, thick or solid walled CNTs; thin diameter or thick diameter CNTs; short or woolen (long) CNTs or any combination thereof.

[0034] According to an embodiment of the present disclosure, a carbon-containing gas may be subjected to an electrolysis process, also referred to herein as an electrosynthesis process, for producing a carbon alkane gel containing a carbon nanomaterial (CNM) product from the carbon in the gas. The term "carbon alkane gel" used herein refers to a mixture of CNM and an electrolyte, which is a product of the electrolysis process and is positioned on the cathode during and after the electrolysis process. The terms "carbon nanomaterial product" and "CNM product" are used herein to refer to a collection of one or more forms of nanocarbon, which may also be referred to as nanoscale carbon. The term "nanocarbon" used herein refers to carbon arranged in a specific structure (such as a graphite nanocarbon structure) at the nanoscale. Specifically, carbon from a carbon-containing gas can be dissociated into carbon and oxygen using a molten electrolyte medium and various electrolysis process configurations. The electrolysis process can cause carbon to be transferred from the gas phase to a molten electrolyte medium, a solid CNM product, or both. The CNM product may be substantially pure, pure, or impure carbon nanomaterial (CNM), including carbon nanotubes (CNTs). The CNM product may include one or more forms of the CNM structure as described above, or any combination thereof. Optionally, one or more parameters of the electrolysis process may be adjusted to alter the relative amount of a given morphology in the CNM product.

[0035] like Figure 1 As shown, the electrolysis process can occur in an apparatus 10, which includes a housing 12 for accommodating a cathode 18, which housing can also be referred to as an electrolysis chamber or electrolysis cell, wherein an anode 16 can form at least a portion of the inner surface of the wall of the housing 12. The two electrodes together define an electrolysis space therebetween. As will be appreciated by those skilled in the art, the anode 16 can optionally be separated from the wall of the housing 12. The housing 12 is configured to accommodate an electrolyte medium 21. The electrolysis space B including the upper surface 21A of the electrolyte can be connected to a carbonaceous gas source (at Figure 1 In some embodiments of the present disclosure, the housing 12 may be contained within an insulating housing 20 made of a thermally insulating material. The insulating housing 20 may also include a top 22 or side or bottom (not shown) that may or may not be made of an insulating material, and the insulation may be a CO2 permeable insulation, such as a high temperature woven ceramic, or a substantially CO2 impermeable insulation. Examples of permeable insulation include, but are not limited to, Morganite made of oxides of aluminum oxide and silicon dioxide. and may include zirconium oxide and Morganite made from alkaline earth metal silicates Both are rated for temperatures in excess of 1200° C. Examples of insulation that is mostly impermeable to CO2 include a wide range of commercially available refractory bricks or cast refractory cements and mortars, and examples include but are not limited to: BNZ material refractory bricks and refractory cements and mortars, such as PA20 and 23, and BNZ2000, 2300, 23A, 2600, 26-60, 2800, 3000 and 3200, rated for temperatures in excess of 1090° C.

[0036] The source of carbon-containing gas can be various industrial plants, including but not limited to: cement manufacturing plants; iron refineries; steel manufacturing plants; plants that manufacture or use one or more of ammonia, ethanol, magnesium, hydrogen, polymers, plastics, glass; wastewater treatment plants, food processing plants. The source of carbon-containing gas can also be chemical reactors, including internal combustion engines and the combustion of carbon-containing materials for heating or cooking. Exhaust gases from power plants, steam power generation facilities, or pyrolysis reactors can also be sources of carbon-containing gas. Carbon-containing gases emitted from these sources or in the production of any high carbon footprint substances can also contribute to or constitute a carbon source for the preparation of CNM products. In addition, gas products of the combustion or conversion of fossil fuels used for heating, transportation, and carbon products such as polymers and plastics can also contribute to or constitute a carbon source for the manufacture of CNM products.

[0037] In some embodiments of the present disclosure, the anode 16 is formed as a planar structure, a wire structure, a wire mesh, a porous structure, a conductive plate, a flat or folded gasket, a coil structure, or the anode can form at least part of the inner side wall of the housing 12. The anode 16 can be formed of various conductive materials so that the anode 16 can generate oxygen or not generate oxygen. Such anode forming materials include, but are not limited to: any conductive material having a stabilizing layer or establishing a highly stable oxide outer layer that is conducive to the generation of oxygen during the electrolysis reaction performed according to the embodiments of the present disclosure, Ni, Ni alloys, galvanized (zinc-coated) steel, titanium, graphite, iron, and a variety of metals, which establish a highly stable oxide outer layer that is conducive to the generation of oxygen. Further examples of suitable materials for forming the anode 16 include nickel alloy 36 (nickel without chromium but containing iron), nickel-chromium alloys (nickel-chromium-based alloys), including stainless steels such as SS 304 or SS 316, and inconel alloys such as inconel 600, 625 and 718, alloy C-264 or nickel-chromium alloys such as Chromel A, B, or as co-nucleation of alloy components is known to produce high-quality CNTs. Binary and ternary transition metal nucleators may also be useful, including but not limited to: Ni, Cr, Sn, In, Fe, and Mo, which may also affect CNM product growth.

[0038] In some embodiments of the present disclosure, a transition metal can be added to the anode 16, which can be dissolved from the anode 16 to migrate to the cathode 18 through the electrolyte medium 21. The added transition metal can act as a nucleating agent, which can be selected from nickel, iron, cobalt, copper, titanium, chromium, manganese, zirconium, molybdenum, silver, cadmium, tin, ruthenium, zinc, antimony, vanadium, tungsten, indium, gallium or non-transition metals such as germanium or silicon or mixtures thereof, including but not limited to brass, Monel alloy (Monel) and nickel alloy. The transition metal can also be directly introduced into the electrolyte medium 21 as a dissolved transition metal salt to migrate to the cathode 18. The transition metal nucleating agent can also be directly added to the cathode 18.

[0039] In some embodiments of the present disclosure, the cathode 18 is formed as a planar structure, a wire structure, a wire mesh, a porous structure, a conductive plate, a flat or folded gasket, a sheet, a coil structure, or the cathode can be formed as at least a portion of the inner side wall of the housing 12. The cathode 18 can be formed of various conductive materials that reflect the needs of the variation of the nucleation point and the CNM product formed on the cathode 18. Such cathode forming materials include, but are not limited to: any conductive material, galvanized (zinc-coated) steel, titanium, graphite, iron, alloys containing copper and zinc, monel (Ni400, Ni / Cu alloy), Inconel, stainless steel, iron, nickel-chromium alloy, pure copper and brass alloy, which may also be suitable as materials for manufacturing the cathode 18.

[0040] Anode 16 and cathode 18 can be aligned substantially parallel to each other in housing 12, such as a stainless steel housing or a housing made of substantially pure or pure alumina. Housing 12 can be made of any material suitable for accommodating molten electrolyte medium 21 and maintaining the temperature reached by device 10A. Electrodes can be oriented in any direction, including but not limited to substantially horizontal or substantially vertical, but spaced apart from each other to define electrolysis space B therebetween. In some embodiments of the present disclosure, electrolysis space B is between about 0.1cm and about 10cm. In some embodiments of the present disclosure, electrolysis space B is about 1cm. As will be appreciated by those skilled in the art, the size of electrolysis space B will be determined by the scale of device 10, such as the size of each electrode, the plenum chamber defined in the housing, the amount of applied current and combinations thereof.

[0041] Anode 16 and cathode 18 are operably connected to a current source (not shown), which can be any source of alternating or direct current (constant or non-constant) providing a current density between about 0.001 A / cm2 and 10 A / cm2. In some embodiments of the present disclosure, the current density provided between the electrodes is at least 0.02 A / cm 2 , 0.05A / cm 2 , 0.1A / cm 2 , 0.2A / cm 2, 0.3A / cm 2 , 0.4A / cm 2 , 0.5A / cm 2 , 0.6A / cm 2 , 0.7A / cm 2 , 0.8A / cm 2 , 0.9A / cm 2 , 1.0A / cm 2 The power source for the current source may be any power source or a combination of multiple power sources, including an electric power source, a solar power source, and the like.

[0042] The heat source (not shown) can be any heat source that raises the temperature within the housing 12 to a temperature that causes the electrolyte medium 21 to transition to a molten phase. For example, the heat source can achieve a temperature of about 500° C. to about 850° C. or more within the housing 12. In some embodiments of the present disclosure, the heating achieves a temperature between about 700° C. to about 800° C., between about 720° C. to about 790° C., or between about 750° C. to about 780° C. In some embodiments of the present disclosure, heating is performed to achieve a temperature of 749-750° C., 751-752° C., 753-754° C., 755-756° C., 757-758° C., 759-760° C., 761-762° C., 763-764° C., 765-766° C., 767-768° C., 769-770° C., 771-772° C., 773-774° C., 775-776° C., 777-778° C., or 779-780° C. In some embodiments of the present disclosure, the temperature within the housing 12 may be increased to about 800° C. or hotter. In some embodiments of the present disclosure, the heat source is provided or supplemented by the exothermic reaction of CO absorption and conversion to carbonate (mass transfer from gas phase to solid phase CNM product) or the overpotential of the applied electrolysis current.

[0043] In some embodiments of the present disclosure, the electrolyte medium may include a carbonate that can be heated by a heat source until it is converted into a molten phase. For example, the carbonate may be lithium carbonate or a lithiated carbonate. Molten carbonates such as lithium carbonate (Li2CO3) (having a melting point of 723°C) or lower melting point carbonates such as LiBaCO3 (having a melting point of 620°C), when containing oxides, include spontaneous oxide formation, which occurs when melted or as a result of electrolysis or when mixed with highly soluble oxides such as Li2O, Na2O and BaO, maintaining rapid absorption of CO2 from the space above the molten electrolyte medium. Suitable carbonates may include alkali carbonates and alkaline earth carbonates. Alkali carbonates may include carbonates of lithium, sodium, potassium, rubidium, cesium or francium, or mixtures thereof. Alkaline earth carbonates may include carbonates of beryllium, magnesium, calcium, strontium, barium or radium, or mixtures thereof. In some embodiments of the present disclosure, the electrolyte may be a mixed composition, such as a mixture of alkali metal carbonates and alkaline earth metal carbonates with one or more of oxides, borates, sulfates, nitrates, chlorides, chlorates, or phosphates.

[0044] According to an embodiment of the present disclosure, the carboalkane gel is formed by electrolytic dissociation of a molten carbonate of CO2. The carboalkane gel includes a mixture of a CNM network and an electrolyte, which is retained after the electrolysis process stops. Interestingly, the carboalkane gel can retain the CNM network after processing (such as crushing). In addition, the electrolyte content of the carboalkane gel (treated or untreated) can be reduced by pressing, reacting or washing the electrolyte. After removing some or all of the electrolyte, the carboalkane gel is composed of CNM, which is composed of high-purity carbon. After removing some or all of the electrolyte, the CNM can define internal voids. For example, the CNM can define void spaces within the CNM, on the surface of the CNM, and within the CNM, or a combination thereof. For the purposes of the present disclosure, the term "void" refers to a two-dimensional or three-dimensional space within the CNM that is substantially free of electrolyte or other substances.

[0045] In some embodiments of the present disclosure, the voids defined within the CNM may be partially, substantially completely filled, or completely filled with a void filler, such as a material based on the application. Examples of suitable void fillers include, but are not limited to, reinforcing agents, catalysts, dopants, drugs, or electromagnetic field (EMF) shielding agents. Reinforcing agents may include, but are not limited to, epoxy compounds, resins and other polymers, gelling materials, and metals. Catalysts may include, but are not limited to, materials that accelerate chemical or electrochemical reactions. Dopants may include, but are not limited to, materials that significantly affect the physicochemical properties of polymer-CNM blends and materials and products made therefrom at low amounts within the voids. The CNM components in the carbazine gel may be mechanically, electrically, or magnetically aligned to further enhance one or more properties of the polymer-CNM blend and materials and products made therefrom, or to impart new properties thereto. Such properties include, but are not limited to, strength, electrical properties, and thermal properties. Electrical and / or magnetic alignment may be achieved by applying a directional electric and / or magnetic field during the carbazine gel preparation stage. Magnetic CNMs are prepared by incorporating magnetic materials (such as metals or metal carbides) into the production of CNMs during an electrolytic process. The polymer-CNM blends can be used to form sheets that can be used alone, such as for liners, thermal retarders or shields, or combined with other materials (not made with the polymer-CNM blends), such as but not limited to laminates, to impart improved properties to those other materials.

[0046] The high production costs of CNM are known to be primarily due to high reactant and energy costs. Without being bound by any particular theory, these production costs can be reduced by two orders of magnitude when produced from CO2 using a molten electrolysis process according to an embodiment of the present disclosure.

[0047] Some embodiments of the present disclosure are directed to a system 200 for preparing a polymer-CNM blend 222. Figure 2 As shown in the non-limiting example of , system 200 includes an apparatus 210 for performing an electrolysis process, a container 212, and a monomer / polymer mixture source 214, wherein the electrolysis process dissociates carbon dioxide (CO2) in a molten electrolyte to produce a carbene gel product. As described below, system 200 can be used to perform the method of the present disclosure.

[0048] In some embodiments of the present disclosure, the device 210 may be the same or similar to the device 10 described above. The device 210 is configured to perform an electrolysis process of dissociating a carbonaceous gas in a molten electrolyte. The dissociated product is a CNM product having a large amount or residual electrolyte therein, i.e., a carbamate gel, which may also be referred to as a carbamate gel product.

[0049] Vessel 212 receives the carboalkane gel (e.g. Figure 2The container 212 may be made of a variety of materials and have any shape and size, provided that the container 212 is strong enough to withstand the temperature of the carboalkane gel received therein.

[0050] The system 200 may also include an isolation unit 224 for protecting the polymer-CNM blend 222 from an oxidizing environment. The isolation unit 224 may include a fluid-tight container having a suitable size to receive the polymer-CNM blend 222 and remove any oxidant (such as an oxygen-containing gas) from the container, for example, by a vacuum pump, and replace the fluid in the container with a non-oxygen-containing gas (such as an inert gas).

[0051] The source of the monomer / polymer mixture 214 can be a container for holding the monomer / polymer mixture, and / or the source 214 can include a preparation unit for preparing the monomer / polymer mixture. For the purposes of the present disclosure, the term "polymer mixture" is used interchangeably with the terms "polymer mixture", "monomer / polymer mixture" and "monomer / polymer mixture" to refer to a polymer, a homopolymer, a heteropolymer, a mixture of at least two polymers, a monomer, at least two monomers, or any combination thereof, wherein the polymer mixture can be used in embodiments of the present disclosure to make a polymer-CNM blend. For example, the preparation unit can include a reaction vessel in which one or more chemical reactions can be performed. Non-limiting examples of such chemical reactions that can be performed in the reaction vessel include, but are not limited to: initiation reactions, propagation reactions, termination reactions, condensation reactions, ring-opening reactions, ionic reactions, chain transfer reactions, photon-based reactions, thermal reactions, plasma polymerization reactions, or any combination thereof.

[0052] Additionally or alternatively, the preparation unit may comprise an extruder for applying predetermined heat and pressure to an extruder input to produce a monomer / polymer mixture.

[0053] The source of monomer / polymer mixture 214 may include monomer precursors that may need to be combined with carboalkane gel before being prepared into polymers in order to produce polymer-CNM blends. Additionally or alternatively, monomer / polymer mixture 214 may include already prepared polymers that can be combined with carboalkane gel for producing polymer-CNM mixtures.

[0054] In some embodiments of the present disclosure, source 214 is a source of natural polymers, synthetic polymers, semisynthetic polymers, recycled polymers, amorphous polymers, semicrystalline polymers, thermosetting polymers, thermosetting polymers, thermoplastic polymers, monomer precursors of such polymers, or any combination thereof.

[0055] In some embodiments of the present disclosure, source 214 is a source of PLA, PVA, PP, PE, acrylic, ABS, nylon, Teflon, PC, epoxy resin, epoxy resin, acrylic, phenolic resin, polysiloxane, polyurethane, polyimide, vulcanized rubber, Bakelite, pDCPD, polyisocyanurate, polyester, polyurea, urea-formaldehyde, vinyl ester, cyanate ester, melamine, polyester resin, monomer precursors of such polymers, or any combination thereof.

[0056] In some embodiments of the present disclosure, the system 200 may further include a processing unit 216 for grinding the cooled or hot carboalkane gel product before (or after) the container 212 receives the cooled or hot carboalkane gel product. The processing unit 216 may be a variety of suitable components, mechanisms or machines that can withstand the temperature of the carboalkane gel, such as but not limited to: a grinder; a shredder; a physical press; a crushing unit; a milling machine or any combination thereof. The degree of the processing operation performed by the processing unit 216 determines the particle size of the resulting carboalkane gel.

[0057] In some embodiments of the present disclosure, the system 200 may further include an electrolyte reduction unit 218. The electrolyte reduction unit 218 may receive the cooled or hot carboalkane gel product directly from the device 210, and / or the electrolyte reduction unit 218 may receive the treated carboalkane gel product from the processing unit 216. The electrolyte reduction unit 218 reduces the electrolyte content of the carboalkane gel product (treated or untreated) so that the carboalkane gel with reduced electrolyte content can be processed (or further processed) in the processing unit 216 and then received in the container 212. Alternatively or additionally, the carboalkane gel with reduced electrolyte content can be received in the container 212 from the electrolyte reduction unit 218.

[0058] The electrolyte reduction unit 218 can reduce the electrolyte content of the carboalkane gel (treated or untreated) by mechanical methods, chemical methods, electrochemical methods, or any combination thereof. For example, the mechanical method may include various suitable components, mechanisms, or machines that can reduce the electrolyte content of the carboalkane gel, such as a mechanical press that pushes the carboalkane gel through a mesh or screen, a heater for melting the electrolyte in the carboalkane gel, a filter (room temperature or high temperature), or any combination thereof. The chemical method for reducing the electrolyte content of the carboalkane gel includes one or more washing stations for exposing the carboalkane gel to one or more chemicals that can dissolve the electrolyte. In addition to reducing the electrolyte content, one or more chemicals can also be applied to dissolve impurities, such as amorphous carbon or metals, from the CNM in the carboalkane gel. The electrochemical method includes a device for performing selective electrolysis to reduce the electrolyte content and / or impurity content of the carboalkane gel.

[0059] In some embodiments of the present disclosure, the system 200 may further include an alignment unit 220 that is configured to align the carbene gel (treated and / or electrolyte-reduced or not) and / or the polymer-CNM blend (e.g. Figure 2 The alignment unit 220 may be integrated into the container 212 so that the alignment process performed by the alignment unit 220 occurs within the container 212. Alternatively or additionally, the alignment unit 220 may be a physical component separate from the container 212 that may receive the uncompressed carboalkane gel (treated and / or electrolyte reduced or not reduced), perform the alignment procedure, and then transfer the aligned carboalkane gel to the container 212. The alignment unit 220 may employ one or more of mechanical methods, electrical methods, magnetic methods, or any combination thereof, so that the aligned CMN component in the polymer-CNM blend has the desired anisotropic properties. The alignment unit 220 may employ mechanical methods through various suitable components, mechanisms, or machines that may apply a directional physical stress field to the CNM within the carboalkane gel (treated and / or electrolyte reduced or not reduced) and / or the CNM within the polymer-CNM blend. For example, the mechanical method may apply a shear force to the CNM product within the carboalkane gel. Shear forces may be applied by pulling, rotating or dragging a body (such as a piston) through the CNMs within the carbene gel (treated and / or electrolyte reduced or not) and / or within the polymer-CNM blend. Alternatively, shear forces may be applied directionally to increase CNM entanglement rather than CNM alignment.

[0060] The alignment unit 220 may employ electrical methods through various suitable components, mechanisms or machines that can apply a directional electric field to the CNMs within the carbene gel (treated and / or electrolyte reduced or not) and / or within the polymer-CNM blend.

[0061] The alignment unit 220 may employ magnetic methods via various suitable components, mechanisms or machines that may apply an oriented magnetic field to the CNMs within the carbene gel (treated and / or electrolyte reduced or not) and / or within the polymer-CNM blend.

[0062] In some embodiments of the present disclosure, the alignment unit 220 may be used to reduce rather than increase the directional alignment of the CNMs, thereby reducing any anisotropic properties of the polymer-CNM blend.

[0063] Figure 3The steps of a method 100 for preparing a polymer-CNM blend are shown, including the steps of receiving a carboalkane gel at 102, combining the carboalkane gel and a monomer / polymer mixture in a container at 108, and recovering the polymer-CNM blend at 110. Optionally, the method 100 may also include the step of producing the carboalkane gel by the electrolysis method described above at 101. The method 100 may also include the step of treating 103 and / or reducing 105 the electrolyte content of the carboalkane gel.

[0064] For receiving step 102, the electrolysis process described above can be used to produce carbene gel, which can be referred to as producing step 101. The produced carbene gel contains entangled products of CNM grown on the cathode during the melt electrolysis dissociation of CO2. By selectively controlling the operating parameters of the producing step 101, the electrolysis process described above, the produced carbene gel can have a large relative amount of the desired morphology of CNM in the carbene gel. For example, compared with other morphologies of nanocarbon structures in the CNM of carbonate nanoshells, the electrolysis process can be controlled to increase the relative amount of spherical nanocarbons, solid and hollow nano-onions, cylindrical allotropes of nanocarbons, planar allotropes, spiral allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanosheets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface-modified or metal-coated CNMs, amorphous nanocarbons without graphitic features or characteristics, or any combination thereof.

[0065] The resulting carbamate gel containing the CNM product can be received in a carbamate gel processing step 103, which includes allowing the carbamate gel to cool, peeling or breaking off pieces of the carbamate gel from the cooled cathode 18, grinding the carbamate gel, or any combination thereof. Alternatively, in the processing step 103, the carbamate gel containing the CNM and containing the hot molten electrolyte product can be extracted from the cathode 18 while still hot, and then the hot carbamate gel is subjected to grinding or other steps of the methods described herein. In this way, the receiving step 102 can be a cooled and solid or hot and thick fluid carbamate gel, which can be subjected to further processing or not.

[0066] According to embodiments of the present disclosure, processing step 103 can be performed by a variety of methods, such as grinding techniques, including but not limited to: grinding; shredding; pressing; crushing; milling or a combination thereof. The resulting particle size of the carboalkane gel material in the carboalkane gel material is determined by the degree of grinding. Further and / or more strictly, grinding will result in a smaller carboalkane gel particle size, which can affect the merging of the polymer mixture and the carboalkane gel compared to a situation where processing step 103 is performed for a shorter amount of time and / or is less strict.

[0067] In some embodiments of the present disclosure, the electrolyte and / or impurity content of the carbene gel can be reduced by reducing step 105. Without limitation, the reduced impurities can include non-graphite carbon, such as amorphous carbon and metals or combinations thereof. Some, most, substantially all or all of the electrolyte and / or impurities can be removed from the carbene gel by pressing, reacting or washing the carbene gel by chemical, mechanical or electrochemical methods. For example, a mechanical method for reducing step 105 can include applying physical pressure to the carbene gel to mechanically force the electrolyte to leave the carbene gel through a sorting device (such as a net with a specific pore size). The mechanical method may also include adjusting the temperature to a temperature above the melting point of the electrolyte to promote electrolyte flow and separation. The melting point range of alkali metal and alkaline earth carbonate electrolytes is from less than 400°C for molten eutectic ternary Li, Na, K carbonates to 891°C for potassium carbonate. The applied pressure can be in the range of 0 to 1000 pounds per square inch (psi), 1000 to 2000 psi, or 2000 or more psi. Alternatively or additionally, reducing 105 may include a chemical method, whereby the carboalkane gel is exposed to one or more chemicals to cause a reaction, thereby reducing the electrolyte content of the carboalkane gel. For example, a washing liquid may be used to wash the carboalkane gel, wherein the washing liquid may dissolve a portion of the residual or bulk electrolyte from the carboalkane gel particles. The washing liquid may include a neutral pH liquid, such as water or a saline solution, or an acidic or alkaline solution that can promote the dissolution of molten electrolytes, such as formic acid or hydrochloric acid or ammonium sulfate, an oxidizing solution, such as permanganate or peroxide, or an organic solvent, or any combination thereof. In addition to reducing the electrolyte, the washing liquid may also be used to dissolve impurities such as amorphous carbon or metals from the CNM. In some embodiments of the present disclosure, the electrolyte content of the carboalkane gel may be reduced by room temperature filtration and / or high temperature filtration. Other methods for reducing the electrolyte content of the carboalkane gel 105 include, but are not limited to: mechanical methods such as screening and filtration; electrochemical means, such as selective electrolysis; thermal means, such as oxidative removal by burning less stable amorphous carbon, which may also be used to remove CNM impurities; or any combination thereof. Reducing the electrolyte content of the carboalkane gel can increase the relative proportion of CNM in the carboalkane gel. In some embodiments of the present disclosure, the step of reducing the electrolyte and / or impurity content of the carboalkane gel 105 can be performed one or more times on the treated or untreated carboalkane gel.

[0068] In one embodiment of the present disclosure, carboalkane gel (treated and / or with reduced electrolyte content or not) is combined with a polymer mixture in a single step to form a polymer-CNM blend. In another embodiment, carboalkane gel (treated and / or with reduced electrolyte content or not) is added during the process of preparing the polymer, such as during the initiation step and / or the development step and / or the termination step of preparing the polymer. In another embodiment, carboalkane gel (treated and / or with reduced electrolyte content or not) is added during the step of preparing the polymer, wherein a condensation reaction / mechanism occurs, a ring-opening reaction / mechanism occurs, an ionic reaction / mechanism occurs, a chain transfer reaction / mechanism occurs, a photon-based reaction / mechanism occurs, a thermal reaction / mechanism occurs, a chemical reaction / mechanism occurs, a plasma polymerization reaction / mechanism occurs, or a combination thereof.

[0069] In some embodiments of the present disclosure, carbazine gel (treated and / or with reduced electrolyte content or not) is added during the preparation of natural, synthetic, semi-synthetic or recycled polymers. In another embodiment of the present disclosure, carbazine gel (treated and / or with reduced electrolyte content or not) is added during the preparation of thermoplastic polymers or thermosetting polymers. In another embodiment of the present disclosure, carbazine gel (treated and / or with reduced electrolyte content or not) is added during the formation of amorphous polymers or semi-crystalline polymers.

[0070] Without being bound by any particular theory, the inventors theorize that the molten residual electrolyte within the treated carbamate gel particles provides a driving force for the uniform dispersion of the CNMs, which, after merging, results in the assembly of the treated carbamate gel particles into the polymer-CNM blend without the need for ultrasonication or other more rigorous mixing processes. The carbamate gel prepared during the electrolysis process for the dissociation of CO2 includes both the CNMs and the electrolyte, and the presence of this merging can provide a fixed structure that is effectively a lattice matrix for the "pre-dispersed" CNMs.

[0071] Example 1: PLA polymer-CNT formation conditions via polymerized carboalkane gel.

[0072] Some embodiments of the present disclosure relate to a method for preparing a polymer-CNT blend, wherein the polymer mixture comprises PLA. During this method, a carbene gel is treated by grinding to form carbene gel particles that are added prior to a polymerization step, and then a polymerization step is performed to form a blend of PLA polymer and CNM of the ground carbene gel. Conventional polymerization preparation of PLA is carried out by one of two pathways, condensation (also known as direct) polymerization or ring-opening polycondensation (also known as ring opening). For example, an aqueous lactic acid solution can be heated and vacuum pumped to remove water, either alone or in the presence of a catalyst. Once the reaction is complete or nearly complete, the liquid PLA (melting at about 130-180° C.) can be poured out or stored for later use as a solid. Either PLA preparation pathway can provide a ground carbene gel initiation and / or development and / or termination stage for PLA formation, such as adding CNM (of the ground carbene gel) to form a PLA-CNM blend.

[0073] CNT is the strongest known material, and significantly enhances the intensity of PLA-CNT blends compared to independent PLA.Usually, CNT is not added to thermoplastics before polymerization, and has added ultrasonic treatment and / or dissolved thermoplastic solvent mixture to allow the uniform dispersion of CNT, or adds sufficient mixing in the melting process before extrusion.On the contrary, as an example of this embodiment, CNT is added as polycarboxylate and polycarboxylate ground, and it is compatible with PLA.Aqueous polycarboxylate superplasticizer, including but not limited to various superplasticizers (such as those commercially available from Adva, Plastol and BASF and other plasticizers) is fabulous carboalkane gel CNM dispersant, can conventional mixing, rather than ultrasonic treatment, cause the substantially uniform dispersion of carboalkane gel / polycarboxylate ground in PLA polymer blend.Therefore, before PLA polymerization, adding carboalkane gel and polycarboxylate ground without wasting energy ultrasonic treatment can provide dispersed CNM in the early stage of PLA formation process and in the whole process. In some embodiments of the present disclosure, ground carbamate gel and / or polycarboxylate are added after the polymerization process, and then the PLA polymer, ground carbamate gel and / or polycarboxylate are subjected to an extrusion process to provide a substantially uniform dispersion of CNMs in the PLA polymer. These alternative ground continuous polymer-CNM blend formation schemes are shown in Figure 6 middle.

[0074] Example 2: Carboalkane gel PLA polymer-CNT formation conditions by extrusion.

[0075] In a further embodiment of the present disclosure, during the polymer extrusion step, crushed carbene gel particles are used to replace conventionally dispersed CNMs to prepare polymer-CNM blends. Extrusion can use a blend of treated carbene gel with a solid polymer or a molten polymer. This embodiment is compared with the conventional process of PLA-CNT blend preparation. In the conventional process, 0, 2, 4, 6 or 8wt% of CNTs are mixed by blending with PLA pellets for 8 hours. Ultrasonic treatment without liquid to transmit sonic energy is impossible in this medium. Although there is no ultrasonic treatment, the extended mixing time by blending is an attempt to achieve uniform dispersion. The known extrusion process uses a twin-screw extruder, followed by a single-screw extruder at a temperature increased from 165°C to 220°C to form a known PLA / CNT blend for testing. 6wt% CNT addition shows the greatest strength increase. Compared with PLA with 0% CNT, 6wt% PLA / CNT blends produce a 64% increase in tensile strength and a 29% increase in flexural strength. Instead of conventional CNTs, in this embodiment of the present disclosure, the processed carbazine gel is added with PLA during blending for extrusion. Thus, using much lower mixing times, such as less than 1 hour, comparable PLA-CNT strength increases can be achieved at substantially the same amount of CNT loading. According to embodiments of the present disclosure, mixing of molten polymer with carbazine gel produces a significant increase in the associated storage modulus.

[0076] Example 3: Thermoset-Carbonane Gel Blends.

[0077] The present embodiment relates to forming a polymer-CNM blend by combining a treated carboalkane gel with a thermosetting plastic (such as an epoxy resin) that cannot be melted and reformed normally. The treated carboalkane gel can be a ground carboalkane gel and provides improved dispersion and interaction with the polymer. For example, in one type of conventional epoxy resin-CNT blend, CNTs (as opposed to carboalkane gel) are uniformly dispersed and then covalently attached to an epoxide-containing component (O cyclic or bonded to two Cs) via an amine connection, followed by the epoxy group reacting to form an epoxy resin-CNT blend. In some embodiments of the present disclosure, the ground carboalkane gel is mixed and dispersed in a solvent to induce defects, CNMs are grafted and / or covalently attached to epoxides (O bonded to two Cs) via functionalized moieties, and the solvent is a compatible medium. This mixing is followed by reacting the epoxide, such as by chemical reaction (including polyamine, polyamide, base or anhydride mediated reactions), thermal based hardeners or photon based hardeners to open the oxygen rings and form an epoxy-CNM blend formed from the ground carbamate gel, rather than conventional CNTs.

[0078] Other embodiments of the present disclosure use mixtures of CNMs with polymers. This is achieved by dispersing the CNMs in the polymer mixture, but here by mixing the ground carbene gel directly into the polymer mixture. Conventional dispersion of CNMs in mixtures is achieved by mechanical or magnetic shear mixing, calendaring, extrusion, ball milling or ultrasonic treatment or a combination thereof, and has been used with direct impregnation or indirect integration to enhance texture.

[0079] Example 4: Increased tensile strength of epoxy-CNM blends.

[0080] Figure 4 Photographs and tensile strength data are shown for examples of epoxy resins with and without added carbazine gel made from CO2 according to embodiments of the present disclosure. Figure 4 The upper small figure shows three products made without carbene gel (three dog-bone products on the left hand side) and three products made with carbene gel according to an embodiment of the present disclosure (three dog-bone products on the right hand side). The carbene gel products are completely black, and the photos are illuminated to highlight the contrast. The carbene gel used to prepare the carbene gel products is made by converting CO2 into carbene gel using an electrolysis process as described herein. Carbene gel is manufactured in a device 10 using a stainless steel housing 304 in a 750°C Li2CO3 molten electrolyte, which has a Muntz brass cathode and a stainless steel 304 anode to produce a CNT carbene gel product. When the cathode becomes a monel alloy or a Ni alloy, including Inconel, a nickel-chromium alloy, and a Ni-iron and a Ni-copper alloy, and the anode becomes an Inconel, a nickel-chromium alloy, a Ni-iron and a Ni-copper alloy, the carbene gel is also made of CO2 to prepare a CNT carbene gel product. This carbene gel product is cleaned with hydrochloric acid (HCl). About 4 parts of Metlab M135 resin and about 1 part of Metlab M135 hardener were degassed separately in a vacuum chamber at 60°C. Then, the desired 0%, 0.05%, 0.1%, 0.25% or 0.5% by weight of purified CNTs containing reduced electrolyte (compared to the total weight of resin and hardener) of carboalkane gel was added to the resin and then mixed at 65 rpm for 4 minutes and then ultrasonicated for 15 minutes. After ultrasonication, the hardener was added, mixed at 65 rpm for 4 minutes, and then degassed. The samples were cured at 60°C for use in conventional "dog bone" molds and removed for tensile strength testing. Figure 4 The top panel shows three cured control samples without added carbazine gel at the top left, and three cured samples with 0.5 wt% carbazine gel at the top right. The tensile strength relative to the control samples was measured with an ETM-10 kN computer controlled electronic universal test production machine. Figure 4The lower panel shows the observed increase in tensile strength compared to the tensile strength of the article without the addition of carbene gel. Figure 4 The lower panel in FIG. 5 shows that samples with 0.05 wt%, 0.1 wt%, 0.25 wt% and 0.5 wt% of carbene gel exhibited 4%, 15%, 21% and 33% relative increases in measured tensile strength, respectively.

[0081] Example 5: Polymer-CNM blends alone and in combination with alternating layers.

[0082] Polymer-CNM blends can be used alone in materials or products such as planar linings, thermal retarders or thermal shields. Polymer-CNM blends can also be used in combination with another material that is not made of polymer-CNM blends, another material such as but not limited to laminates, where the polymer-CNM blends impart new or improved properties to those other materials. For example, polymer-CNM blends and composites thereof exhibit shape memory properties under various activation conditions such as thermal activation, mechanical activation, electrical activation, magnetic activation, photoactivation or chemical activation. The shape memory property can be incorporated into polymer-CNM blends, materials or products made therefrom, and materials or products made by combining polymer-CNM blends (or their materials or products) with another material. Note that in addition to shape memory properties, when epoxy resin is used as a polymer in a polymer-CNM blend, when the CNM contains multi-walled CNTs, with the addition of 0.1-1wt%, there may be an increase in tensile strength of up to 184% and an increase in impact strength of up to 444%, which is produced by selecting the operating conditions of the electrolysis process. Furthermore, when the operating conditions of the electrolysis process are selected to increase the relative amount of coiled CNTs within the CNM, there can be an enhanced spring effect. As described above, these shape memory properties can also be enhanced by incorporating anisotropic properties into polymer-CNM blends through alignment. The electrical and thermal conductivity of CNMs (such as graphene) can present superior properties for their use as polymer heating elements or heat sinks. Combining shape memory properties and heating element behavior can be used each alone or in combination with a layer of another material.

[0083] Figure 5 is an example of a carbon alkane gel in which the electrolyte has been reduced by washing and is shown at two different magnifications of x720 and x8600 as measured by scanning electron microscopy SEM. This example is a CNT carbon alkane gel prepared by CO2 electrolysis in the previous example. Figure 5In the upper panel of FIG. 1 , the large particle size of the CNM blended with the carbazine gel is evident. This is large compared to conventional filter media porosity and provides a rare opportunity for nano-sized CNMs to be macroscopically processed for blending onto polymers. In addition to the advantage of being formed from CO2 rather than high carbon footprint reactants, this allows the carbazine gel to be easily formed from microscopically constrained filters despite the carbazine gel material being nano-sized, as shown in FIG. Figure 5 After electrolysis, the carbene gel was processed by stripping it from the cooled cathode and breaking it up. After washing with concentrated HCl, Figure 5 The SEM image of the treated carbene gel is shown in Figure 1. The high purity of the CNTs and their orientation in a range of different directions are shown in Figure 1. Figure 5 It is also obvious in the. Alternative washing with dilute HCl acid similarly washes away electrolyte and metal impurities, as measured by electron dispersion spectroscopy (EDS) and thermogravimetric analysis (TGA). Alternative washing with water or formic acid or ammonium sulfate mainly removes excess electrolyte and does not remove any metal impurities. Another alternative washing combining hydrochloric acid and hydrogen peroxide, in this case, ultrasonic treatment, rather than mixing carbene gel in a solution of concentrated HCl and 35% H2O2, removes excess electrolyte, metal impurities and additional amorphous carbon impurities. Similarly, it is observed that other chemical oxidants, such as hydrochloric acid and potassium permanganate, are effective in the case of sufficient dilution, as are electrochemically generated oxidants. When measured with TGA, amorphous carbon has a lower combustion temperature than carbon nanotubes, and amorphous carbon is more easily oxidized than more solid graphite nanocarbon structures (such as layered graphene CNT structures). Therefore, impurity amorphous carbon can be removed by chemical oxidation, electrochemical oxidation, thermal oxidation or any combination thereof. As a further example, the impurity content of the carboalkane gel was reduced by heating the carboalkane gel to 300°C after the HCl wash. The reduced impurity content was measured by the mass reduction of the carboalkane gel observed after the impurity reduction step and by TGA and SEM. The TGA data showed that the HCl and the heating step for reduction largely removed the amorphous carbon impurities, and the SEM analysis showed that the carbon nanoparticles with reduced impurity content retained CNTs.

[0084] Without being bound by any particular theory, the polymer-CNM blends of the present disclosure may be used in polymer material and polymer product applications while increasing the environmental sustainability of such polymer materials and polymer products made therefrom by: (i) reducing the input materials required to make the polymer material or polymer product since the carboalkane gel content will impart enhanced strength and / or conductivity; (ii) allowing the polymer material and polymer product to last longer through enhanced chemical, mechanical, light and thermal resistance while still being as easily recyclable as currently available polymer materials and products made without the carboalkane gel of the present disclosure; (iii) replacing less environmentally friendly polymers, such as polyethylene, with the polymer-CNM blends of the present disclosure, such as PLA-CNM blends; (iv) applications of such polymer materials and polymer products acting as carbon-sealed storage layers, or any combination thereof.

[0085] The CNM-polymer blends prepared according to embodiments of the present disclosure can be used in various materials and product applications, such as but not limited to: linings, thermal retarders or shields. However, according to embodiments of the present disclosure, polymer-CNM blends, materials and products made therefrom can also be used as components in composite materials, such as but not limited to: laminates, which contain at least one layer made of polymer-CNM blends and other non-CNM materials to impart improved properties to those other non-polymer materials. In addition, polymers made from polymer-CNM blends and composite materials made from such polymers (including CNM) exhibit shape memory properties under thermal, mechanical, electrical, magnetic, optical or chemical activation conditions, and these properties can be imparted to materials or products incorporating (by impregnation or reinforcement or otherwise integrating) such CNM (including polymers). As described above, the shape memory effect is promoted by incorporating anisotropic properties into polymers made from polymer-CNM blends. In addition, the electrical conductivity and thermal conductivity of the CNM polymer product can provide excellent properties when used in heating element or radiator applications.

[0086] Other applications of materials and products made from the polymer-CNM blends of the present disclosure that can utilize the excellent CNM properties imparted by carbazine gels include, but are not limited to: (i) lightweight tool applications for high speed, safety, and quick change; (ii) harder tools for better drilling, impacting, and / or sawing; (iii) tools with better thermal management; (iv) ultra-strong foldable materials; (v) general sequestration of CO2; (vi) ultra-light, super-absorbent sponges; (vii) as prefabricated laminates for inclusion in composite materials; (viii) for ballistic or electromagnetic field (EMF) shielding; (ix) parachutes and drag enhancers; (x) weavable / seamable polymers for textiles / fabrics; or (xi) fibers / filaments for 3D manufacturing or printing.

[0087] According to embodiments of the present disclosure, other uses of materials and products made using polymer-CNM blends include products that combine the advantages of two or more excellent CNM-based properties, such as: providing a dual-use structural material, additionally reducing weight, material cost / use, and / or increasing capacity. Some non-limiting examples of such dual uses include: (i) using strength properties for structural purposes and using electrical energy storage properties; (ii) using strength properties for structural purposes and using thermal energy storage properties; (iii) using strength properties for structural purposes, used as electrical conduits or wires; (iv) using strength properties for structural purposes and used as sensors to collect real-time strain or safety data to evaluate the properties of the material; (v) using strength properties for structural purposes and as catalysts; (vi) using strength properties for structural purposes and as heat conduits or any combination thereof. In addition, according to embodiments of the present disclosure, there are applications and uses of materials and products made using polymer-CNM blends to improve safety by heat dissipation components used to dissipate high heat, such as in applications where fire is a concern.

Claims

1. A method for preparing a polymer-carbon nanomaterial (CNM) blend, the method comprising the following steps: (a) receiving a carboalkane gel product, wherein the carboalkane gel product comprises CNM dispersed in an electrolyte, wherein the carboalkane gel product is produced by dissociating carbon dioxide (CO2) through a melt electrolysis process; (b) combining the carbene gel product with a polymer mixture; and (c) Collecting the polymer-CNM blend.

2. The method according to claim 1, further comprising a preparation step for preparing the polymer mixture.

3. The method according to claim 2, wherein: The polymer mixture comprises one or more polymer precursors, and the preparing step occurs after the step of combining the carboalkane gel product with the polymer mixture.

4. The method according to claim 2, wherein: The preparing step occurs prior to the step of combining the carbene gel product with the polymer mixture.

5. The method of claim 4 further comprising the step of extruding the combined carbene gel product and polymer mixture.

6. The method of claim 1 further comprising the step of treating the carbamate gel product prior to the step of combining the carbamate gel product with the polymer mixture.

7. The method according to claim 6, wherein: The steps of processing the carbene gel product include grinding, chopping, pressing, pulverizing, milling, crushing or a combination thereof.

8. The method of claim 1, further comprising the step of reducing the electrolyte content of the carbamate gel product.

9. The method according to claim 8, wherein: The reducing step includes pressing, reacting, washing, filtering or any combination thereof.

10. The method of claim 1 further comprising the step of applying heat after the step of receiving the carbazine gel product, wherein The heat is a temperature between 0°C and 1000°C.

11. The method according to claim 1, wherein: The polymer mixture is prepared by a condensation mechanism, a ring opening mechanism, an ionic mechanism, a chain transfer photon mechanism, a thermal mechanism, a chemical mechanism, a plasma polymerization mechanism, and any combination thereof.

12. The method according to claim 1, wherein: The polymer-CNM blend comprises from 10 wt % CNM to less than 10 wt % CNM.

13. The method according to claim 1, wherein: The carbene gel product includes entangled products of CNMs.

14. The method according to claim 1, wherein: The received carbon alkane gel product includes CNM, which includes spherical nanocarbons, solid nano-onions, hollow nano-onions, cylindrical allotropes of nanocarbons, planar allotropes of nanocarbons, spiral allotropes of nanocarbons, carbon nanotubes (CNTs), nanofibers, graphene, nanosheets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanorods, surface-modified or metal-coated CNMs, amorphous nanocarbons without graphitic features, and any combination thereof.

15. The method according to claim 1, wherein: The polymer mixture includes natural polymers, synthetic polymers, semi-synthetic polymers, recycled polymers or any combination thereof.

16. The method according to claim 1, wherein: The polymer mixture includes an amorphous polymer, a semi-crystalline polymer, or any combination thereof.

17. The method according to claim 1, wherein: The polymer mixture includes a thermosetting polymer, a thermoplastic polymer, or any combination thereof.

18. The method according to claim 1, wherein: The polymer mixture comprises at least one of PLA, PVA, PP, PE, acrylic, ABS, nylon, Teflon, PC, epoxy resin, acrylic, phenolic resin, polysiloxane, polyurethane, polyimide, vulcanized rubber, Bakelite, polydicyclopentadiene, polyisocyanurate, polyester, polyurea, urea-formaldehyde, vinyl ester, cyanate ester, melamine, polyester resin or any combination thereof.

19. The method of claim 1 further comprising the step of applying an alignment force to the carbene gel product.

20. The method according to claim 19, wherein: The alignment force is applied by one or more of mechanical force, electric current, magnetic field, or any combination thereof.

21. The method according to claim 19, wherein: The aligning force has a linear geometry, a radial geometry, a cylindrical geometry, a spherical geometry, or other geometry to produce a linear, radial, cylindrical, spherical, or other directional geometry to produce one or more anisotropic characteristic properties of the polymer-CNM blend.

22. The method of claim 1 further comprising the step of applying a void filler for partially or substantially completely filling voids within the polymer-CNM blend, on the surfaces of the CNMs of the blend, within the interior spaces of the CNMs of the blend, or any combination thereof.

23. The method according to claim 22, wherein: The gap filler is a reinforcing agent, a catalyst, a doping agent, a magnetic material, a drug, an electromagnetic force shielding enhancer and any combination thereof.

24. The method according to claim 22, wherein: The void filler includes resin, gelling material, metal, alloy or any combination thereof.

25. The method according to claim 23, wherein: The dopant includes boron, nitrogen, sulfur, phosphorus, cobalt, aluminum, silicon, cerium, platinum, gold, ruthenium, osmium, tellurium, tungsten, corresponding oxides, corresponding salts or any combination thereof.

26. The method of claim 23, wherein: The magnetic material is iron, nickel, cobalt, gadolinium, samarium, neodymium, steel, corresponding carbides, other alloys containing one or more magnetic materials with ferromagnetic properties, paramagnetic properties, diamagnetic properties, and any combination thereof.

Citation Information

Patent Citations

  • Methods and systems for production of doped carbon nanomaterials

    CN110312678A

  • Use of carbon nanomaterials produced with low carbon footprint to produce composites with low co2 emission

    CN112912337A